2023
DOI: 10.1021/acsaem.2c03453
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mitigation of Transient Phenomena That Complicate the Characterization of Halide Perovskite Photodetectors

Abstract: Halide perovskites have shown promise to advance the field of light detection in next-generation photodetectors, offering performance and functionality beyond what is currently possible with traditional inorganic semiconductors. Despite a relatively high density of defects in perovskite thin films, long carrier diffusion lengths and lifetimes suggest that many defects are benign. However, perovskite photodetectors show detection behavior that varies with time, creating inconsistent device performance and diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
(145 reference statements)
0
8
0
Order By: Relevance
“…The LDR of 2D/3D perovskite devices increased particularly in the weak light intensity range. The trap-assisted nonradiative losses can reduce the charge carrier collection efficiency, leading to undesired nonlinear responses at low light powers. , As the light power increases, the trap states are filled, resulting in a saturation operation. Therefore, we attributed the enhanced weak light detection capability of the IPA-BAI PD to the significant reduction of trap states after mixed-phase 2D perovskite modification.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The LDR of 2D/3D perovskite devices increased particularly in the weak light intensity range. The trap-assisted nonradiative losses can reduce the charge carrier collection efficiency, leading to undesired nonlinear responses at low light powers. , As the light power increases, the trap states are filled, resulting in a saturation operation. Therefore, we attributed the enhanced weak light detection capability of the IPA-BAI PD to the significant reduction of trap states after mixed-phase 2D perovskite modification.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recent works on PDs explain the origin of the initial peak well in terms of capacitive effects. These photocharging features can be due, for example, to the separation of electron and hole distributions in organic semiconductors. , It is well-known that the capacitance in halide perovskite measured by impedance spectroscopy is a strong function of incident light and shows very large values. As mentioned before, in perovskite PDs, it has been observed that the large capacitance has a predominant effect. , For simplicity, we describe the capacitive effect with a simple constant capacitor C m that represents the low-frequency capacitance of the device. The transient dependence of the capacitance on light is ignored in the first approximation.…”
Section: Modelmentioning
confidence: 99%
“…Ideally, a fully flat current response is required, but measurements made over many years with silicon, organic, and perovskite PDs show a number of distinct characteristics. , In addition, the detection behavior of perovskite PDs exhibits temporal variations and current drift. These features often result in significant challenges in the characterization of device performance. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead-based metal halide perovskites with the general structural formula ABX 3 have received widespread attention from the scientific community in recent years due to their excellent optoelectronic properties, and they have been used in solar cells, light-emitting diodes, photodetectors and other fields [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Although remarkable achievements have been made in the field of optoelectronic applications, the inherent toxicity and instability of lead-based materials limit their further practical applications [15,16].…”
Section: Introductionmentioning
confidence: 99%